Cairo cosmopolitan : politics, culture, and urban space in the new globalized Middle East - Singerman, Diane; Amar, Paul (Paul Edouard), 1968- (American University in Cairo Press, 2006)
Giving the reader an idea of the huge size of Cairo and its leading position as a metropolis in the Middle East as a whole, this book is written mostly by Egyptians and particularly residents of Cairo.